2000
DOI: 10.1007/s10434-000-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Paclitaxel and Radiotherapy for Locally Advanced Breast Cancer: Surgical Aspects

Abstract: Preoperative paclitaxel with radiotherapy is well tolerated and provides significant pathological response, in up to 33% of patients with locally advanced breast cancer, but with a significant postoperative morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Chemoradiation toxicity was mainly dermatitis within the RT field, similar to what was reported by Bellon et al 2 Several important differences, however, exist between their retrospective series and the current prospective study. 21 It is reassuring to note that tolerance to postoperative AT or AC was very good; grade 4 leukopenia was observed in 10% of patients, and no other grade 4 toxicity was observed. Moreover, their total dose (50 to 54 Gy compared with 45 Gy in the current study) and technique of RT (use of bolus in 60% of patients) may explain the fact that in 38% of patients, breaks were required during the course of RT therapy, with a median duration of 8 days.…”
Section: Discussionsupporting
confidence: 91%
“…Chemoradiation toxicity was mainly dermatitis within the RT field, similar to what was reported by Bellon et al 2 Several important differences, however, exist between their retrospective series and the current prospective study. 21 It is reassuring to note that tolerance to postoperative AT or AC was very good; grade 4 leukopenia was observed in 10% of patients, and no other grade 4 toxicity was observed. Moreover, their total dose (50 to 54 Gy compared with 45 Gy in the current study) and technique of RT (use of bolus in 60% of patients) may explain the fact that in 38% of patients, breaks were required during the course of RT therapy, with a median duration of 8 days.…”
Section: Discussionsupporting
confidence: 91%
“…A study published in 1999 by the same authors showed an increased pCR rate of 26% after neoadjuvant treatment with paclitaxel and EBRT of the whole breast up to 45 Gy [40]. In the study by Aryus et al comparing combined neoadjuvant radiochemotherapy to chemotherapy alone, the authors were able to show a significant difference between the two groups: patients treated with radiochemotherapy had a pCR rate of 43%, compared to only 6% of patients in the chemotherapy group.…”
Section: Discussionmentioning
confidence: 64%
“…In studies using neoadjuvant combined radiochemotherapy, rates of histopathologic complete remission ranged from 8.6% to 43% [2,8,15,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skinner studied paclitaxel based neoadjuvant chemotherapy and radiotherapy as primary treatment in 29 patients, 27 of whom went on to either BCS or modified radical mastectomy . While clinical responses occurred in 89% and 33% had significant pathological response, surgical complications occurred in 41% in all types of surgery.…”
Section: Introductionmentioning
confidence: 99%